Low potassium intake and its association with blood pressure among adults in Malaysia: findings from the MyCoSS (Malaysian Community Salt Survey) - Lalitha Palaniveloo; Rashidah Ambak; Fatimah Othman; Nor Azian Mohd Zaki; Azli Baharudin; Nur Shahida Abdul Aziz; Ruhaya Salleh (BMC, 2021)
Abstract Background High blood pressure or hypertension is well recognized as an important modifiable risk factor for cardiovascular diseases. Several studies had indicated potassium intake has a blood pressure lowering effect. This study aimed to estimate potassium intake via 24-h urinary potassium excretion and to determine the association between potassium intake and blood pressure among adults in Malaysia. Methods Data for 424 respondents in this study were drawn from MyCoSS, a nationwide cross- sectional study conducted among Malaysians who were 18 years and above. Respondents were recruited using stratified cluster sampling, covering urban and rural areas in each state in Malaysia. Data collection was undertaken from October 2017 until March 2018. A single urine sample was collected over 24 h for quantification of potassium excreted. Information on socio-demography and medical history of the respondents were collected by interviewer-administered questionnaires. Anthropometric measurements were measured using validated equipment. BMI was estimated using measured body weight and height. Digital blood pressure monitor (Omron HBP-1300) was used to measure blood pressure. Descriptive statistics, analysis of variance (ANOVA), and multivariable linear regression were used to analyze the data in SPSS Version 21. Results Mean 24-h urinary potassium excretion for the 424 respondents was 37 mmol (95% CI 36, 38). Gender and ethnicity showed statistically significant associations with 24-h urinary potassium excretion. However, potassium excretion was not significantly associated with blood pressure in this study. Conclusion Potassium intake is very low among the adults in Malaysia. Therefore, further education and promotional campaigns regarding daily consumption of potassium-rich diet and its benefits to health need to be tailored for the Malaysian adult population.